(untitled) (Medico Legal Update, 2023)
Background: Persistent use of lip cosmetics makes them one of the most regular evidence in crime against females, with this concern, plenteous work has been done to differentiate various types of lip cosmetics on basis of their composition. However, the forensic and DNA perspective regarding the same remains unexplored to a huge extent. Study: We looked at the DNA implications of lip stains as well as several ways for extracting DNA from lip cosmetic prints in this work. Conclusion: We came to the conclusion that DNA profiles created from lip cosmetics imprints are extremely valuable in forensic examination for personal identification because they are regarded the most crucial type of transmission traces and are equivalent to finger-marks.